The Joshua generation: Israeli occupation and the Bible - Havrelock, Rachel S. (Princeton, USA: Princeton University Press, 2022)
"The Joshua Generation examines the book of Joshua's many lives, from its relationship to ancient political forms to the present Israeli Occupation. Its scope encompasses the nationalist celebrations and the stringent critiques of the biblical volume along with their impacts on political discourse and lived space"--
Includes index.
Keywords: Bible. -- Criticism, interpretation, etc; Arab History; Israeli Conflict; War